(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: Dialysis is procedure that removes excess fluid and the toxic end products of metabolism. The major forms of dialysis are hemodialysis, and peritoneal dialysis. Access to the blood circulation is achieved by the use of central venous catheter or artificial arteriovenous fistula. Objective: To detect and compare prevalence of complications occurs in uremic patients using central venous catheter or arteriovenous fistula in dialysis unit in Al-Kadhimiya Teaching Hospital. Patients and methods: One hundred patients with renal failure (chronic or acute) undergoing hemodialysis were questioned and examined for the Complications occurred during or after the hemodialysis process using arteriovenous fistula or temporary vascular access. Results: The results showed significant of fever and blood flow obstruction in temporary vascular access (<0.05) as a complications in hemodialysis. Other complications such as hepatitis (B&C), hypotension, exit site infection, nausea, itching, muscle cramp, vomiting, backache, fainting and disequilibrium syndrome are similar in arteriovenous fistula and temporary vascular access. Conclusion: The main complications during hemodialysis in this study were fever, malfunction of the catheter, and exit site infection in catheter more common in temporary Catheter than arteriovenous fistula so advice to do arteriovenous fistula before end stage renal disease Keywords: Hemodialysis, arteriovenous fistula and temporary catheter.